PAI-1 is a Critical Upstream Regulator of the TGF-β1/EGF-Induced Invasive Phenotype in Mutant p53 Human Cutaneous Squamous Cell Carcinoma. (19th March 2007) - Wilkins-Port, Cynthia E.; Higgins, Craig E.; Freytag, Jennifer; Higgins, Stephen P.; Carlson, J. Andrew; Higgins, Paul J.
Abstract : The emergence of highly aggressive subtypes of human cutaneous squamous cell carcinoma (SCC) often reflects increased autocrine/paracrine TGF-β synthesis and epidermal growth factor receptor (EGFR) amplification. Cooperative TGF-β /EGFR signaling promotes cell migration and induces expression of both proteases and protease inhibitors that regulate stromal remodeling resulting in acquisition of an invasive phenotype. TGF-β 1+EGF stimulation increases the production of several matrix metalloproteinases (MMPs) in human SCC. Among the most prominent is MMP-10 which is known to be elevated in SCC in situ. Activation of stromal plasminogen appears to be critical in triggering downstream MMP activity. Paradoxically, PAI-1, the major physiological inhibitor of plasmin generation, is also up-regulated under these conditions and is an early event in progression of incipient epidermal SCC. A model is proposed in which TGF-β 1+EGF-dependent MMP-10 elevation directs focalized matrix remodeling events that promote epithelial cell plasticity and tissue invasion. Increased PAI-1 expression serves to temporally and spatially modulate plasmin-initiated pericellular proteolysis, further facilitating epithelial invasive potential. Defining the complex signaling mechanisms that maintain this elegant balance is critical to developing potential therapeutics for the treatment of human cutaneous malignancies.